Molecular dynamics simulation studies of GLUT4: substrate-free and substrate-induced dynamics and ATP-mediated glucose transport inhibition. - Suma Mohan (PLoS ONE, 2010)
BACKGROUND: Glucose transporter 4 (GLUT4) is an insulin facilitated glucose transporter that plays an important role in maintaining blood glucose homeostasis. GLUT4 is sequestered into intracellular vesicles in unstimulated cells and translocated to the plasma membrane by various stimuli. Understanding the structural details of GLUT4 will provide insights into the mechanism of glucose transport and its regulation. To date, a crystal structure for GLUT4 is not available. However, earlier work from our laboratory proposed a well validated homology model for GLUT4 based on the experimental data available on GLUT1 and the crystal structure data obtained from the glycerol 3-phosphate transporter. METHODOLOGY/PRINCIPAL FINDINGS: In the present study, the dynamic behavior of GLUT4 in a membrane environment was analyzed using three forms of GLUT4 (apo, substrate and ATP-substrate bound states). Apo form simulation analysis revealed an extracellular open conformation of GLUT4 in the membrane favoring easy exofacial binding of substrate. Simulation studies with the substrate bound form proposed a stable state of GLUT4 with glucose, which can be a substrate-occluded state of the transporter. Principal component analysis suggested a clockwise movement for the domains in the apo form, whereas ATP substrate-bound form induced an anti-clockwise rotation. Simulation studies suggested distinct conformational changes for the GLUT4 domains in the ATP substrate-bound form and favor a constricted behavior for the transport channel. Various inter-domain hydrogen bonds and switching of a salt-bridge network from E345-R350-E409 to E345-R169-E409 contributed to this ATP-mediated channel constriction favoring substrate occlusion and prevention of its release into cytoplasm. These data are consistent with the biochemical studies, suggesting an inhibitory role for ATP in GLUT-mediated glucose transport. CONCLUSIONS/SIGNIFICANCE: In the absence of a crystal structure for any glucose transporter, this study provides mechanistic details of the conformational changes in GLUT4 induced by substrate and its regulator.